Determination of Coastal Belt in the Disaster Prone Area: A case study in the Coastal area of Bantul Regency, Yogyakarta, Indonesia - Arief Widianto; Michiel Damen (Indonesian Journal of Geography, 2014)
Mitigation strategy development is needed for protecting coastal communities and preserving coastal resourc-es from the impact of coastal hazards. It is believed that coastal land use planning can be proposed to reduce impact of coastal hazards. ἀe coastal belt boundary development is one of the mitigation approach which is common use in many countries as an inexpensive solution compared to hard structure development. Our study was located in the coastal area of Bantul regency, a low lying coastal area and densely populated region, where some clustered people lives proximity to the sea. In this study, a new method for determining coastal belt boundary was developed in the study area. ἀe Spatial Multi Criteria Evaluation (SMCE) tool of Ilwis plays as powerful tool for assessing coastal vulnerability in term of multi-hazard events. To calculate the width of the coastal belt boundary, the Ilwis-SMCE outcomes were employed. By apply-ing this method, there were three scenarios of the setbacks wide for both direct and pairwise method to be proposed. In general, the coastal area of Bantul Regency is dominated by high vulnerable area respectively impacted by multi-hazard events (tsunami, high wave and erosion-accretion), by incorporating some coastal features, such as topography, bio-physics, economic, and social-culture. ἀe results of the analysis are consistent with what was observed in the actual areas. Taken into account for hazard and vulnerability indices, the coastal belt boundary established in this area should wider than those already determined by existing regulations.